A multicentre study of 95 biopsy-proven cases of renal disease in primary Sjögren's syndrome. (7th December 2016) - Jasiek, Magali; Karras, Alexandre; Le Guern, Véronique; Krastinova, Evguenia; Mesbah, Rafik; Faguer, Stanislas; Jourde-Chiche, Noémie; Fauchais, Anne-Laure; Chiche, Laurent; Dernis, Emmanuelle; Moulis, Guillaume; Fraison, Jean-Baptiste; et al.
Abstract : Objective. Renal involvement is a rare event during primary SS (pSS). We aimed to describe the clinico-biological and histopathological characteristics of pSS-related nephropathy and its response to treatment. Methods. We conducted a French nationwide, retrospective, multicentre study including pSS patients fulfilling American–European Consensus Group criteria or enlarged American–European Consensus Group criteria, and with biopsy-proven renal involvement. Results. A total of 95 patients were included (median age 49 years). An estimated glomerular filtration rate (eGFR) of <60 ml/min was found in 82/95 patients (86.3%). Renal biopsy demonstrated tubulointerstitial nephritis (TIN) in 93 patients (97.9%), and frequent (75%) plasma cell infiltrates. Glomerular lesions were found in 22 patients (23.2%), mainly related to cryoglobulin. The presence of anti-SSA (76.8%) and anti-SSB (53.8%) antibodies was particularly frequent among patients with TIN and was associated with a worse renal prognosis. Eighty-one patients (85.3%) were treated, with CSs in 80 (98.8%) and immunosuppressive agents (mostly rituximab) in 21 cases (25.9%). Despite marked interstitial fibrosis at initial biopsy, kidney function improved significantly during the 12-month period following diagnosis (final eGFR 49.9 vs 39.8 ml/min/1.73 m 2 at baseline, P < 0.001). No proven benefit of immunosuppressive agents over steroid therapy alone was found in this study. Conclusion. Renal involvement of pSS is mostly due to TIN with marked T, B and especially plasma cell infiltration. Renal dysfunction is usually isolated but can be severe. Use of CSs can improve the eGFR, but further studies are needed to define the best therapeutic strategy in this disease.